2022
DOI: 10.1021/acs.jpcc.2c05055
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Grain Boundary Passivation and Charge Distribution in Perovskite Films Improved with Anti-solvent Treatment

Abstract: Owing to the polycrystalline nature of hybrid perovskite thin films, the trap states in grain boundaries (GBs) introduced by charged defects play an important role in determining the charge collection efficiency and have a significant impact on their optoelectronic properties. Herein, we show the direct imaging of the GB passivation of perovskite films through an anti-solvent treatment and the anomalous charge distribution across the films due to the passivation. The downward band bending at the GBs has been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Conversely, the films with KHFDFmodified, the GBs had a higher potential compared to the GIs, which revealed that the additives of KHFDF have the ability to passivate GBs and improve the CPD of GB. [64,65] Meanwhile, from the histograms in Figure 5g,h, we can observe that the films incorporated with KHFDF exhibit a much higher surface potential and a smaller range of CPD distribution relative to the FAMA films, which not only confirmed the UPS conclusions, but also indicated improved charge transport, suppressed carrier recombination and more homogeneous electronic properties. Furthermore, K + ions are seen to be mainly at the top and bottom surface interfacial regions of the perovskite layer, which can interact with undercoordinated I − and inhibit I − migration.…”
Section: Resultssupporting
confidence: 64%
“…Conversely, the films with KHFDFmodified, the GBs had a higher potential compared to the GIs, which revealed that the additives of KHFDF have the ability to passivate GBs and improve the CPD of GB. [64,65] Meanwhile, from the histograms in Figure 5g,h, we can observe that the films incorporated with KHFDF exhibit a much higher surface potential and a smaller range of CPD distribution relative to the FAMA films, which not only confirmed the UPS conclusions, but also indicated improved charge transport, suppressed carrier recombination and more homogeneous electronic properties. Furthermore, K + ions are seen to be mainly at the top and bottom surface interfacial regions of the perovskite layer, which can interact with undercoordinated I − and inhibit I − migration.…”
Section: Resultssupporting
confidence: 64%
“…The uniform current distribution and the overall current signal enhancement of the films after Tb‐cpon modification indicate that the conductivity of the films is improved. [ 43 ] In particular, the films have a stronger current signal at the GBs, which may be attributed to the reduced resistance due to the increased contact area of the conducting tip with the film. Figure 4f shows real‐time photos of different perovskite films annealed at 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Different techniques or compounds have been used to passivate the defects in the surface as well as the bulk along with grain boundaries. TAS is used to understand the type of defects and changes in defect states due to the passivation effect. To get a clear insight into the hole extraction process at the interface, TAS can be used to probe the perovskite/HTL interface, which allows probing of the excited-state dynamics on different time scales. It is proven that surface passivation is more effective than bulk passivation in improving the PSC performance.…”
Section: Introductionmentioning
confidence: 99%